(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In article the estimation of perspective possibilities and strategy of a phenomenon of individuality in the conditions of social reforming of Kazakhstan is spent. It is shown that from the point of view of evolution of interrelation of the person and a society as the basic link of process of updating reconsideration a parity individual and public should act.